A Novel Finding of Tribological and Mechanical Linking to Micro‐Convex Texture on Hydrophilic Composites Surface under Water‐Lubricating Conditions. Issue 5 (26th December 2021) - Liang, Xiang; Guo, Zhiwei; Li, Zhe; Qiu, Yikun; Wang, Zhikang; Yuan, Chengqing
Abstract: The existence of micro‐structures endows the materials with some novel characteristics. In this study, the hot‐spot material thermoplastic polyurethane (TPU) is used as the experimental object, and the water‐lubricating composites are prepared by introducing well‐hydrophilic polyvinyl alcohol (PVA) fibers, which can spontaneously and continuously produce micro‐convex textures in water. By observing and analyzing the internal structures, physical and chemical properties, coefficient of friction, wear surface, wear loss, etc. of the materials, the relationship between the micro‐convex structures on the material surface and its tribological properties is studied. The experimental results show that the existence of micro‐convex structures can make the material show better wear resistance during the friction process, and they will not disappear completely with the process. The most obvious effect is the sample containing 15% PVA fibers and with soaking and polishing treatments, its coefficient of friction is 0.11, which is 74.42% lower than that of the pure sample without any treatments, the main reason is due to the hydrodynamic lubrication effect and cavitation effect of the micro‐convex structures. For the wear mechanism, pure samples are adhesive wear, and modified samples are mainly abrasive wear. This work will provide new design ideas for tribology in the micro‐nano field. Abstract : Here, a hydrophilic macromolecular composite is designed, whose surface can spontaneously produce many micron‐level micro‐convex textures in a water‐lubricated environment, and the relationship between the hydrophilic macromolecular composite surface and its tribological and mechanical properties at several stages before and after the formation of micro‐convex textures is studied. Further, the different action mechanisms during this process are identified.